PENYERAPAN TENAGA KERJA PADA SEKTOR PERTANIAN DAN SEKTOR JASA PASCAKEBIJAKAN UPAH MINIMUM DI PROVINSI BANTEN (PERIODE TAHUN 2001–2011) - Muhammad Findi Alexandi; Ovilla Marshafeni (Jurnal Manajemen & Agribisnis, 2013)
ABSTRACTThe purpose of this study was to analyze the conditions of employment and the factors that affect employment in agriculture and services in the province of Banten. The method used was descriptive analysis and regression analysis of panel data. The estimation results showed that all variable of the minimum wage in districts/ cities, consumption, investment, and gross regional domestic product (GDP) significantly affect employment in agriculture and services in the province of Banten. Factors affecting employment in agriculture and the service sector in the province of Banten are as follow: First, the agricultural sector model estimation results indicate that UMK variable, consumption, investment, and GDP have significant effect on employment in the agricultural sector. Second, the service sector model estimation results indicate that UMK variable, consumption, investment, and GDP have significant effect on employment in the agricultural sector. Therefore, the Government of Banten Province is expected to increase the growth rate and GDP contribution of the agricultural sector and the service sector, taking into account the level of wages and observing conditions of employment in that sector.Keywords: agriculture sector, labor, employment, GDP, Banten ABSTRAKTujuan  dari penelitian ini adalah menganalisis kondisi ketenagakerjaan dan faktor-faktor yang memengaruhi penyerapan tenaga kerja di sektor pertanian dan jasa di Provinsi Banten. Metode yang digunakan analisis deskriptif dan analisis regresi data panel. Hasil estimasi semua variabel upah minimimum kabupaten/kota, konsumsi, investasi, dan Produk Domestik Regional Bruto (PDRB) berpengaruh nyata terhadap penyerapan tenaga kerja di sektor pertanian dan jasa di Provinsi Banten. Faktor-faktor yang memengaruhi penyerapan tenaga kerja sektor pertanian dan sektor jasa di Provinsi Banten adalah sebagai berikut. Pertama, hasil estimasi model sektor pertanian menunjukan bahwa variabel UMK, konsumsi, investasi, dan PDRB memiliki pengaruh yang signifikan dalam penyerapan tenaga kerja di sektor pertanian. Kedua, hasil estimasi model sektor jasa menunjukan bahwa variabel UMK, konsumsi, investasi, dan PDRB memiliki pengaruh yang signifikan dalam penyerapan tenaga kerja di sektor pertanian. Oleh karena itu, Pemerintah Provinsi Banten diharapkan mampu meningkatkan laju pertumbuhan dan kontribusi PDRB sektor pertanian dan sektor jasa, memperhitungkan tingkat upah, dan memerhatikan kondisi lapangan pekerjaan di sektor tersebut.Kata kunci: sektor pertanian,  tenaga kerja, upah minimum, PDRB, Banten